Theoretical Foundations of Efficiently Organizing Production Processes: Using the Example of Combining Organizational Forms of Component Manufacture and Internal Transport - Schroeder, Anne-Katrin; Nebl, Theodor; Mainzinger, Christian (Journal of Industrial Engineering, 2014)
This paper examines the problem of efficient production processes organization down to subprocesses levels. Subtasks of production within subprocesses necessitate a specific set of requirements for production organization. Through particular features and their respective characteristics, these requirements are further systemized and described as process types. The main manufacturing process “component manufacture” and its connected production support service “internal transport” have been chosen as examples to show relevant organizational principles and forms. From this baseline and together with a decision algorithm, selected organizational options and a combination thereof shall lead to theoretically optimized solutions which meet all predefined requirements. A multilevel organizational alignment model lays out interdependencies of combined process type-oriented organizational forms. Methods of comparative organizational profile analysis in support of reengineering approaches are systemized and further developed towards resulting organizational adaptations.